Organizing a PhD symposium—an inside view: Setting up a scientific meeting is challenging—a PhD symposium offers its own unique opportunities and pitfalls. (17th September 2013) - Schröder, Markus S; Harnett, Dermot; Minke, Benedikt A; Nair, Preethy Sasidharan; ,
Abstract : Planning a symposium organized by PhD students is a challenging prospect. Insight from the organizers of three such symposia sheds light on the highs and lows of the experience.